Liquidity and Ambiguity: Banks or Asset Markets? - Jürgen Eichberger; Willy Spanjers (University of Heidelberg, Department of Economics, 2007)
We study the impact of ambiguity on two alternative institutions of financial intermediation in an economy where consumers face uncertain liquidity needs. The ambiguity the consumers experience is modeled by the degree of confidence in their additive beliefs. We analyze the optimal liquidity allocation and two institutional settings for implementing this allocation: a secondary asset market and a bank deposit contract. For full confidence we obtain the well-known result that consumers prefer the bank deposit contract over the asset market, since the former can provide the optimal cross subsidy for consumers with high liquidity needs. With increasing ambiguity this preference will be reversed: the asset market is preferred, since it avoids inefficient liquidation if the bank reserve holdings turn out to be suboptimal.
Keywords: D8; G1; G2; 330; Financial institutions; Liquidity; Ambiguity; Choquet Expected Utility; Finanzintermediation; Kapitalanlage; Entscheidung unter Unsicherheit; Liquiditätspräferenz; Bankgeschäft; Finanzmarkt; Theorie